Effectiveness of application of a manual for improvement of alarms management by nurses in Intensive Care Units - Amirhossein Yousefinya; Camellia Torabizadeh; Farid Zand; Mahnaz Rakhshan; Mohammad Fararooei (Universidad de Antioquia, 2021)
Objective. To evaluate the effects of application of a manual on the improvement of alarms management in Intensive Care Units (ICU). Methods. This quasi-experimental study evaluated the effectiveness of the introduction into of a manual for alarm management and control in the ICU of a hospital in southeastern Iran. The intervention was a 4-hour workshop was on topics related to the adverse effects of alarms, standardization of ECG, oxygen saturation and blood pressure monitoring systems, and the use of ventilators and infusion pumps. Data were collected thorough 200 hours of observation of 60 ICU nurses (100 hours' pre-intervention and 100 hours' post-intervention). Response time, type of response, customization of alarm settings for each patient, the person responding to an alarm, and the cause of the alarm were analyzed. Alarms were classified into three types: false, true and technical. Results. The results showed a statistically significant difference between the pre- and post-intervention frequency of alarm types, frequency of monitoring parameters, customized monitoring settings for patients, and individuals who responded to alarms. The percentage of effective interventions was significantly higher for all parameters after the intervention (46.9%) than before the intervention (38.9%). Conclusion. The employment of a manual for management of alarms from electronic equipment in ICUs can increase the frequency of appropriate responses to alarms in these units.